1993
DOI: 10.1029/93jb00349
|View full text |Cite
|
Sign up to set email alerts
|

Nature of seismic coupling along simple plate boundaries of the subduction type

Abstract: The downdip width of the seismogenic zone is defined for 19 subduction zones. This width is measured from the base of the accretionary prism to the maximum depth of nucleation of thrust events along the plate boundary. Those two points are taken to define the upper and lower depth transitions from stable to unstable frictional sliding. The lower depth transition is found to be between 35 and 70 km. The dip angle of the thrust zone is also reevaluated. We find a linear increase in the dip angle as a function of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
375
4
10

Year Published

1999
1999
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 431 publications
(429 citation statements)
references
References 75 publications
34
375
4
10
Order By: Relevance
“…Moreover, the experimental negative relation between energy release (i.e., stress drop) and driving rate (Figure 3) for intermediate-to-high values of the latter parameter is consistent with the nonlinear relation between seismicity in subduction zones and relative plate velocity. This observation highlights the complex role played by subduction velocity in tuning seismic interplate behavior, explaining why faster subduction zones (i.e., Tonga, New Hebrides) are not associated with powerful activity [Pacheco and Sykes, 1992;Pacheco et al, 1993;Gutscher and Westbrook, 2009;Heuret et al, 2011].…”
Section: Implications For Subduction Zone Seismogenesismentioning
confidence: 99%
“…Moreover, the experimental negative relation between energy release (i.e., stress drop) and driving rate (Figure 3) for intermediate-to-high values of the latter parameter is consistent with the nonlinear relation between seismicity in subduction zones and relative plate velocity. This observation highlights the complex role played by subduction velocity in tuning seismic interplate behavior, explaining why faster subduction zones (i.e., Tonga, New Hebrides) are not associated with powerful activity [Pacheco and Sykes, 1992;Pacheco et al, 1993;Gutscher and Westbrook, 2009;Heuret et al, 2011].…”
Section: Implications For Subduction Zone Seismogenesismentioning
confidence: 99%
“…Studies of interplate seismicity have shown that large earthquakes generally initiate within specific depth limits, generally between ~10 and 40 km (Byrne et al, 1988;Pacheco et al, 1993;Tichelaar and Ruff, 1993;Scholz, 2002), but the precise limits vary with temperature (Hyndman et al, 1997). This observation led to a conceptual model in which the subduction thrust is divided into three zones (e.g., Scholz, 1988).…”
Section: Background Seismogenesis At Convergent Marginsmentioning
confidence: 99%
“…For many subduction zone thrust faults there is an updip limit, seaward of which there is little or no seismicity (Figure 1) [House andJacob, 1983; Byrne et al, 1988; Byrne andFisher, 1990; Pacheco et al, 1993]. The updip aseismic zone could result from thrust contact with accretionary prism sediments where stable sliding is taken to be a property of unconsolidated However, this depth range represents only about :1:10-20 km in the landward seismogenic limit because of the quite steep dip of the thrusts at these depths.…”
Section: Updip Temperature Limitmentioning
confidence: 99%